Assessing the fit of RapidSMS for maternal and new-born health: perspectives of community health workers in rural Rwanda. Issue 1 (2nd January 2016) - Mwendwa, Purity
ABSTRACT: This article examines field results that show the potential for mobile health (mHealth) technologies to support community health workers (CHWs) in delivering basic maternal and new-born services in Rwanda. The fit of RapidSMS, a UNICEF/Ministry of Health (MOH) mHealth technology is examined through focus groups with CHWs. The results highlight the need for more training in the use of RapidSMS, continued upgrading of mobile phones, devising innovative ways of charging mobile phones, and ensuring the availability of ambulances. We suggest that CHW supervision be a two-way process built into RapidSMS utilising real-time communication to enhance effectiveness.